Future role and economic benefits of hydrogen and synthetic energy carriers in Germany: a review of long-term energy scenarios. (March 2023) - Scheller, Fabian; Wald, Stefan; Kondziella, Hendrik; Gunkel, Philipp Andreas; Bruckner, Thomas; Keles, Dogan
Abstract: Determining the development of Germany's energy system is the subject of a series of studies. Since their results play a significant role in the political energy debate for understanding the role of hydrogen and synthetic energy carriers, a better discussion is needed. This article provides an assessment of published transition pathways for Germany to assess the role and advantages of hydrogen-based carriers. Twelve energy studies including 37 scenarios for the years 2030 and 2050 were evaluated. Despite the variations, the carrier will play an important role. While their deployment is expected to have only started by 2030 with a mean demand of 91 TWh/a ( ∼ 4% of the final energy demand) in Germany, they will be an essential part by 2050 with a mean demand of 480 TWh/a ( ∼ 24%). The outcome of the scenarios depends on the chosen methods and assumptions. A moderately positive correlation (0.53) between the decarbonisation targets and the share of hydrogen-based carriers in final energy demand underlines the relevance for reaching the climate targets. Additionally, value creation effects of about 16 billion EUR/a in 2050 can be expected for hydrogen-based carriers. Hydrogen is expected to be produced domestically while synthetic fuels are projected to be mostly imported. Highlights: Economic benefits of hydrogen and synthetic carriers are determined for Germany based on 37 scenarios. Hydrogen and synthetic demand vary between methods and average 91 (480) TWh/a for 2030 (2050). Share of hydrogen-based carriers in final energy demand correlates positively with emissions reductions. Value creation effects of 5 bn EUR/a for 2030 and 16 bn EUR/a for 2050 are calculated for Germany.